Pengembangan Modul Nilai Karakter Mandiri Peserta Didik Melalui Layanan Bimbingan Klasikal - Muhammad Azis; Elni Yakub; Fadhila Rahman (Universitas Batanghari Jambi, 2026)
This research aims to develop a module on independent character values for students through classical guidance services. The study employed a Research and Development (R&D) model using the Four-D approach (Define, Design, Develop, and Disseminate), although only the first three stages were implemented. The research subjects were students of SMP IT Al-Fityah Pekanbaru. Data were collected through interviews, observations, and questionnaires, and the module was validated by media experts, material experts, and linguists. The findings show that the developed module achieved a very high level of validity, with an average validity score of 95.785% across the three validators. Specifically, the media expert provided a validity score of 95.27%, while the material and language experts each assessed it at 96.30%. These results indicate that the module is feasible for use as a practical guideline in implementing classical guidance services, as it meets the required standards of content, design, and linguistic quality. Furthermore, the module is considered effective as an innovative form of guidance and counseling service that is adaptive to current educational developments and capable of enhancing students’ independent character covering emotional independence, behavioral independence, and independence in moral values.